A Study to Assess the Knowledge Regarding Pradhan Mantri Jan Arogya Yojana (PM-JAY) Among the General Public in a Tertiary Care Teaching Hospital, Kuppam - M. Melvin David; T.K. Sreedevi; K. Daniel Arun Kumar; M. Abhirami; M.N. Pavithra; R. Aruna Kumari; S. Subhavelvizhi; P. Steffi (International Journal of Community Health Nursing And Practices, 2026)
Background: Ayushman Bharat, the flagship scheme of the Government of India, was launched to achieve Universal Health Coverage (UHC) as per the National Health Policy 2017. It aims to address healthcare needs comprehensively by transitioning from fragmented approaches toward a holistic system. Pradhan Mantri Jan Arogya Yojana (PM-JAY) is a pivotal component of this scheme, striving to achieve UHC by providing comprehensive healthcare services to underprivileged families. Assessing public awareness and understanding of PM-JAY is crucial for its successful implementation. This study aimed to evaluate the knowledge regarding PM-JAY among the general public in a tertiary care teaching hospital in Kuppam. Methods: A descriptive cross-sectional research design was employed over a three-month period from November 2023–January 2023. The study population comprised visitors to a tertiary care teaching hospital in Kuppam, with a sample size of 386 selected using purposive sampling. Data on demographic variables and PM-JAY knowledge levels were collected using structured questionnaires containing 25 items. Statistical analysis, including frequency, percentage distribution, and chi-square tests, were conducted using SPSS to describe the data and determine associations between demographic factors and PM-JAY knowledge levels. Results: The majority of participants were females (73.8%) and aged over 25 years (59.8%). A significant proportion were daily wage laborers (29.3%) and had a family income of ≤ Rs. 15,000 (64%). The study revealed that 83.7% of the general public had inadequate knowledge regarding PM-JAY, while only 16.3% had moderate knowledge. Statistical analysis showed a significant association between the level of knowledge and age, gender, occupation, family income, area of residence, and type of family (p Conclusion: The study highlights significant demographic disparities in the knowledge of PM-JAY among the general public visiting a tertiary care teaching hospital in Kuppam. These findings underscore the need for targeted interventions to improve awareness and understanding of the scheme, particularly among younger individuals, males, those in certain occupations and income groups, and residents of rural areas. Enhanced awareness is crucial for the effective utilization of PM-JAY and the achievement of universal health coverage.
Keywords: Ayushman Bharat; PM-JAY; Pradhan Mantri Jan Arogya Yojana; healthcare awareness; tertiary care hospital